Genome-Wide Association Study Using Individual Single-Nucleotide Polymorphisms and Haplotypes for Erythrocyte Traits in Alpine Merino Sheep - Zhu, Shaohua; Guo, Tingting; Zhao, Hongchang; Qiao, Guoyan; Han, Mei; Liu, Jianbin; Yuan, Chao; Wang, Tianxiang; Li, Fanwen; Yue, Yaojing; Yang, Bohui (Frontiers in Genetics, 2020)
Adaptation to high-altitude hypoxia is essential for domestic animals living on high plains, such as yak, Tibetan chicken, and Tibetan sheep, it ensures oxygen absorption and utilization. Red blood cells are the primary medium for transporting oxygen in the blood. However, little is known about the genetic mechanism of erythrocyte traits. Genome-wide association studies (GWAS) based on single markers or haplotypes have identified potential mechanisms for genetic variation and quantitative traits. To identify loci associated with erythrocyte traits, we performed a GWAS based on method of single marker and haplotype in 498 Alpine Merino sheep for 6 erythrocyte traits: red blood cell count (RBC), hemoglobin (HGB), hematocrit (HCT), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), and RBC volume distribution width coefficient of variation (RWD_CV). Forty-two significant SNPs (single nucleotide polymorphism) associated with 6 erythrocyte traits were detected through single-marker GWAS, thirty-four significant haplotypes associated with 5 erythrocyte traits were detected through haplotype analysis. We identified 6 genes (DHCR24, SPATA9, FLI1, PLCB1, EFNB2 and SH2B3) as potential genes of interest via gene function annotations, location and expression variation. In particular, FLI1 and PLCB1 were associated with hematopoiesis and erythropoiesis, respectively. These results provide a theoretical basis for analyzing erythrocyte traits and high-altitude hypoxia adaptation in Alpine Merino sheep, and provide a useful research reference for plateau livestock studies.